2015
DOI: 10.1016/j.jare.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Strength development in concrete with wood ash blended cement and use of soft computing models to predict strength parameters

Abstract: In this study, Wood Ash (WA) prepared from the uncontrolled burning of the saw dust is evaluated for its suitability as partial cement replacement in conventional concrete. The saw dust has been acquired from a wood polishing unit. The physical, chemical and mineralogical characteristics of WA is presented and analyzed. The strength parameters (compressive strength, split tensile strength and flexural strength) of concrete with blended WA cement are evaluated and studied. Two different water-to-binder ratio (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 17 publications
4
75
0
1
Order By: Relevance
“…Several researchers carried out investigations to know the feasibility of WA usage as a SCM in concrete. [39][40][41][42][43][44]. From the results obtained from various tests, it was concluded that WA can be used as a promising SCM in concrete and the optimum percentage of WA addition was found to be in the range of 10-12%.…”
Section: A Rice Husk Ashmentioning
confidence: 99%
“…Several researchers carried out investigations to know the feasibility of WA usage as a SCM in concrete. [39][40][41][42][43][44]. From the results obtained from various tests, it was concluded that WA can be used as a promising SCM in concrete and the optimum percentage of WA addition was found to be in the range of 10-12%.…”
Section: A Rice Husk Ashmentioning
confidence: 99%
“…Therefore, Chen and Biljana (2014) noted that due to the high amount of silica in wood ash, it can replace cement in the manufacture of cement-bonded composites. In a study to determine strength development in concrete with ash-blended cement, Chowdhury et al (2014) reported that wood ash possesses cement properties and it can augment the role cement plays in the production of wood-cement composite. Thomas (2007) explained that wood ash is a pozzolan, which reacts with water and calcium hydroxide released by the hydration of cement to produce various calcium-silicate hydrates (C-S-H) and hardened concrete.…”
Section: Chemical Constituents Of the Three Timbersmentioning
confidence: 99%
“…Therefore, more calcium silicate hydrate (CSH) was produced. This product was deposited in the pore system, making the cement paste more homogeneous and denser than the control concrete [32].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The G-BRHA was less reactive due to its higher LOI content and lower SiO 2 content compared with those of RHA. In the case of the U-BRHA concrete, its splitting tensile strength was lower and it could be due to poor bonding in the matrix [32] and also the U-BRHA produced the weakest points in the hardened matrix due to its porous structure [33]. However, even though its improvements in strength were lower than that of control concrete, after 7 days the strength of the U-BRHA increased with increasing age, which indicated a slow pozzolanic reaction.…”
Section: Splitting Tensile Strengthmentioning
confidence: 99%